2020
DOI: 10.1021/acssuschemeng.0c00551
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Catalysts for Chemical CO2 Recycling: A Step Forward in the Methanation and Reverse Water–Gas Shift Reactions

Abstract: Advanced catalytic technologies are crucial to enable the transition toward a low-carbon industry with minimized CO 2 emissions. This paper showcases the application of highly effective Ru-promoted Ni-based catalysts for gas-phase CO 2 upgrading: CO 2 methanation and reverse water−gas shift. The addition of small amounts of Ru results in a remarkable enhancement of CO 2 conversion and selectivity. The bimetallic Ru-Ni catalyst displays greater metallic dispersion, tuned electronic properties and outstanding st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 40 publications
0
53
0
Order By: Relevance
“…Pastor-Pérez et al [ 69 ] prepared Fe and Co modified Ni catalysts supported on CeO 2 -ZrO 2 and observed a negative effect of Fe addition, since the 3% Fe, 15% Ni/CeO 2 -ZrO 2 catalyst exhibited lower values for CO 2 conversion and CH 4 selectivity compared to the monometallic Ni catalyst. Likewise, le Saché et al [ 70 ] observed that Fe addition on a Ni/CeO 2 -ZrO 2 catalyst led to a drop in CO 2 conversion and CH 4 selectivity. Furthermore, Frontera et al [ 71 ] also reported a drop in CO 2 methanation activity upon Fe alloying over Ni catalysts supported on Gd-doped CeO 2 (GDC).…”
Section: Promotion With Transition Metalsmentioning
confidence: 98%
See 1 more Smart Citation
“…Pastor-Pérez et al [ 69 ] prepared Fe and Co modified Ni catalysts supported on CeO 2 -ZrO 2 and observed a negative effect of Fe addition, since the 3% Fe, 15% Ni/CeO 2 -ZrO 2 catalyst exhibited lower values for CO 2 conversion and CH 4 selectivity compared to the monometallic Ni catalyst. Likewise, le Saché et al [ 70 ] observed that Fe addition on a Ni/CeO 2 -ZrO 2 catalyst led to a drop in CO 2 conversion and CH 4 selectivity. Furthermore, Frontera et al [ 71 ] also reported a drop in CO 2 methanation activity upon Fe alloying over Ni catalysts supported on Gd-doped CeO 2 (GDC).…”
Section: Promotion With Transition Metalsmentioning
confidence: 98%
“…Renda et al [108] also showed that using ruthenium acetylacetonate instead of ruthenium chloride as the Ru precursor salt could improve the dispersion of the active metals, due to the templating effect of the precursor salt, leading to an enhanced methanation performance. In another interesting study, le Saché et al [70] reported that Ru addition on a Ni/CeO2-ZrO2 catalyst could improve the dispersion of Ni and increase the overall intrinsic activity for the reduction of CO2. The bimetallic NiRu catalyst exhibited enhanced CO2 methanation performance in terms of CO2 conversion and CH4 selectivity at lower temperatures compared to the monometallic Ni catalyst.…”
Section: Promotion With Rumentioning
confidence: 99%
“…It is reasonable for the Ni species with the electron deficient state to possess high catalytic performance for RWGSR when Ni is added as a second metal component to the Mo/Al 2 O 3 catalyst (Kharaji et al, 2014). As for RuNi/CeZr catalyst, the addition of Ru enhances the Ni reducibility and leads to greater Ni dispersion on the catalyst surface, thus promoting overall activity and CO selectivity for the RWGSR (Sache et al, 2020). Typically, MOF-74 plays a role in helping adsorb and deliver electrons, whereas the low amount of Au@Pd NPs in Au@Pd@MOF-74 results in the poor photon adsorption strength of the Au@Pd active sites.…”
Section: Bimetallic Effectmentioning
confidence: 99%
“…Ruthenium is one of the most used noble metals for this purpose. The addition of Ru to an Ni catalyst enhances the Ni reducibility and dispersion on the catalyst surface [76,77] and increases the catalytic activity at a low temperature in CO 2 methanation [53,74]. In dry reforming of methane (DRM), the addition of Ru modifies the interaction between Ni and the support, improving catalyst stability and catalytic performance.…”
Section: Ru/ni Catalysts For Low-temperature Co 2 (Co) Methanationmentioning
confidence: 99%
“…However, they did have some important advantages. The 1% Ru-15% Ni/CeZr system can be used in both CO 2 methanation and RWGS reactions [77]. It is extremely stable and maintained a CO 2 conversion of 53% at 350 • C in methanation (selectivity to CH4: 93%), while maintaining a CO 2 conversion of 72% at 700 • C in a RWGS reaction (selectivity to CO: 91%).…”
Section: Ru/ni Catalysts For Low-temperature Co 2 (Co) Methanationmentioning
confidence: 99%